2022
DOI: 10.1038/s41598-022-12061-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation and resting state fMRI analysis of virtual reality based training in Parkinson’s disease through a randomized controlled trial

Abstract: There are few studies investigating the short-term effects of Virtual Reality based Exergaming (EG) on motor and cognition simultaneously and pursue the brain functional activity changes after these interventions in patients with Parkinson’s Disease (PD). The purpose of this study was to investigate the synergistic therapeutic effects of Virtual Reality based EG on motor and cognitive symptoms in PD and its possible effects on neuroplasticity. Eligible patients with the diagnosis of PD were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…6-8,27,28,35-38,43,46-48,53,56,60,63,64,66,68,71,73,74,77 Twenty-four trials (31 comparisons) involving 1044 participants compared 2 different exercise groups. 6,27,33,34,41,42,44,45,49-52,54,55,57-59,61,62,65,67,69-72,75-78…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6-8,27,28,35-38,43,46-48,53,56,60,63,64,66,68,71,73,74,77 Twenty-four trials (31 comparisons) involving 1044 participants compared 2 different exercise groups. 6,27,33,34,41,42,44,45,49-52,54,55,57-59,61,62,65,67,69-72,75-78…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen trials reported neurochemical outcomes, that is, trophic factors, 8,34,38,49,56,63,72,73,77 oxidative stress, 35,43,49,63,64 and/or inflammatory markers, 34,38,49,72,73,77 with most not reporting medication status when outcomes were taken. Ten trials reported neuroimaging outcomes, that is, brain functional activation, 53,54,56,69,70,75 connectivity, 48,57,58,65,68,78 structure, 48,60 or volume 48,60 measured through fMRI or functional near-infrared spectroscopy in 1 trial, 69 mostly “on” medication 54,56-58,60,65,69,70,75 ; and dopamine receptor binding 7,53 measured “off” medication through positron emitted tomography. Neuroimaging trials examined different brain networks and used different imaging techniques and analysis methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same sliding workflow was considered with samplings of 10, 20, 30, 50, 124, and 188 patients. The choice of such different sizes was based on previous neuroscience studies that used fMRI of similar sample sizes, respectively [119][120][121][122][123][124].…”
Section: Sliding Windows and Overlapping Sliding Windowsmentioning
confidence: 99%